A comparison of scheduling, work hours, overtime, and work preferences across four cohorts of newly licensed Registered Nurses. (8th May 2019) - Stimpfel, Amy Witkoski; Fletcher, Jason; Kovner, Christine T.
Abstract: Aims: To conduct a comparative analysis of four cohorts of newly licensed Registered Nurses and their work schedule, daily shift length, weekly work hours, second job, and weekly overtime hours. Nurses also reported their preferences regarding work schedule and daily shift length. Design: We used a retrospective, comparative design analysing four cross‐sectional surveys from new nurses first licensed between 2004–2015. Methods: Using state licensure lists, nurses who were first licensed between 1 August 2004 and 31 July 2005 were randomly sampled using a nested design in 23 geographical areas in 13 states and Washington, DC. The same sampling strategy was conducted for subsequent cohorts in January 2009, 2012, and 2016. We sent a mailed survey measuring demographics, education, work attributes, and attitudes to participants with a $5 incentive, following methods by Dillman. Results: There were no statistically significant differences in average weekly work hours (39.4 hrs) or holding more than one job for pay (11.6–14.6% across all cohorts). There were statistically significant differences in overtime across cohorts and shift length by unit type. The preferred shift length was 12 hrs and day shift was the preferred work schedule. Conclusion: New nurses are predominantly scheduled for 12‐hrs shifts and nearly half work weekly overtime, trends that have remained relatively stable over the past 10 years. Nurse managers, policy‐makers, and researchers should pay attention to new nurses' schedule and shift preferences and guard against mandatory overtime hours. Abstract : 目的: 对四组新注册护士的工作时间、日班时长、周工作时间、第二职业、周加班时间进行对比分析。护士们还报告了他们对工作时间和日班长度的偏好。 设计: 我们采用评估性、对比设计, 分析了2004年至2015年首次获得执业资格的新护士的四项横断面调查。 方法: 使用州许可证清单, 在2004年8月1日至2005年7月31日期间首次获得执业资格的护士使用嵌套设计在13个州和华盛顿特区的23个地理区域进行随机抽样。在2009年1月、2012年1月和2016年1月对随后的队列进行了相同的抽样策略。我们按照Dillman的方法, 通过电子邮件向参与者发送了一份调查问卷, 测量其人口统计学特征、教育程度、工作性质和态度, 奖金为5美元。 结果: 每周平均工作时间(39.4小时)或一份以上带薪工作(不同队列11.6‐14.6%)没有统计学上的显著差异。不同队列的加班时间和单位类型的轮班时长差异具有统计学意义。首选轮班时间为12小时, 白班是首选工作时间。 结论: 新护士主要安排12小时轮班和每周近一半的工作加班, 这一趋势在过去10年中保持相对稳定。护士长、政策制定者和研究人员应注意新护士的时间表和轮班偏好, 并防止出现强制加班的情况。